Butyrate production enhancement by Clostridium tyrobutyricum using electron mediators and a cathodic electron donor - Choi, Okkyoung; Um, Youngsoon; Sang, Byoung In (Wiley - V C H Verlag GmbbH & Co., 2012)
Electron mediators and electron supply through a cathode were examined to enhance the reducing power for butyrate production by an acidogenic clostridium strain, Clostridium tyrobutyricum BAS 7. Among the tested electron mediators, methyl viologen (MV)-amended cultures showed an increase of butyrate productivity (1.3 times), final concentration (1.4 times), and yield (1.3 times). The electron flow altered by MV addition from the ferredoxin pool to the NADH pool was shown by one electron model, implying that more available NADH increased butyrate production. In the cathode compartment poised at -400?mV versus the Ag/AgCl electrode, the neutral red (NR)-amended cultures of Clostridium tyrobutyricum BAS 7 increased butyrate concentration (from 5 to 8.8?g/L) and yield (from 0.33 up to 0.44?g/g) with no acetate production at all. Given that electrically reduced NR (NRred, yellow) by the cathode was re-oxidized (NRox, red) in the cells on the basis of color change, electron flow from NRred to NAD+ (i.e., NADH generation) induced an increase in butyrate production. This is the first report to show the increase of butyric acid production by electrically driven acidogenesis. These results show that the electron flow altered NADH formation by electron mediators and by the cathodic electron donor, increasing the yield and selectivity of reduced end-products like butyrate. Biotechnol. Bioeng. 2012; 109: 2494-2502. (c) 2012 Wiley Periodicals, Inc.